Effect of Counselling on Social Adjustment of Underachievers - Ameen, Muskan; Khan, Mahmood Ahmad (International Journal of Psychosocial Rehabilitation, 2020)
The present study was undertaken to study the Effect of Counselling on Social Adjustment of Underachievers. An experimental research method was adopted for conduct of the study. The initial sample comprised of 441 high school students of 9th class from two educational zones viz. Baramulla and Singpora Kallan of District Baramulla. Raven’s Advanced Progressive Matrices (Non-Verbal) was administered for the measurement of intelligence. Mean of two annual examination results (7th & 8th) was considered as the criterion for academic achievement. The subjects whose academic achievement scores lie 10th percentile or more below their intelligence percentile scores were considered as underachievers. The final sample comprised of 164 underachievers who were divided into experimental and control groups (n= 82 each). Qadri’s Urdu Adaptation of Bell’s Adjustment Inventory was employed for the measurement of Social Adjustment (Pre-test). Individual counselling was provided to each sample subject in experimental group by making use of eclectic approach of counselling. Counselling process continued for forty two days. The post-test was conducted by again employing Qadri’s Urdu Adaptation of Bell’s Adjustment Inventory. ‘t’ test was employed to see the effect of counselling. The results revealed that counselling has significantly increased the social adjustment of underachievers (experimental group).